Immunosuppression of canine renal allograft recipients by CD4 and CD8 monoclonal antibodies. - Watson, C; Cobbold, S; Davies, H; Rebello, P; Thiru, S; McNair, R; Rasmussen, A; Waldmann, H; Calne, R; Metcalfe, S (1994)
A state of tolerance to MHC mismatched allografts can be generated in rodents by treatment with CD4 and CD8 monoclonal antibodies (mAb). In order to transpose this type of therapy to large animals and ultimately to the clinic, a suitable model is required. To this end we have generated a series of mAb to the canine CD4, CD8, and Thy-1 antigens and have tested their ability to prevent rejection of renal allografts. Donor-recipient pairs were selected from a colony of mongrel dogs in which untreated rejection of two haplotype-mismatched kidneys occurred by day 7 (defined as a serum creatinine > 300 mumol/l). Therapy with either the CD4 or the CD8 mAb, using no other immunosuppression, did not prolong graft survival. Depletion of T cells by a Thy-1 mAb prior to surgery only extended graft survival to day 9. However, treating with combinations of mAb up to day 10 (CD4 plus Thy-1; CD4 plus CD8; or CD4 plus CD8 plus Thy-1) prolonged renal allograft function up to 25 days. Combination of the triple mAb therapy with a sub-therapeutic immunosuppressive drug regimen (cyclosporin A plus azathioprine that alone gave a median survival of 15 days) favored survival to a median of 38 days. This protocol also inhibited the antiglobulin response that had curtailed the effects of mAb treatment, opening the way to more extended, and potentially tolerizing, mAb plus drug regimens.